2018
DOI: 10.1371/journal.pone.0203211
|View full text |Cite
|
Sign up to set email alerts
|

Role of S1P/S1PR3 axis in release of CCL20 from human bronchial epithelial cells

Abstract: BackgroundSphingosine kinase phosphorylates sphingosine to generate sphingosine 1 phosphate (S1P) following stimulation of the five plasma membrane G-protein-coupled receptors. The objective of this study is to clarify the role of S1P and its receptors (S1PRs), especially S1PR3 in airway epithelial cells.MethodsThe effects of S1P on asthma-related genes expression were examined with the human bronchial epithelial cells BEAS-2B and Calu-3 using a transcriptome analysis and siRNA of S1PRs. To clarify the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…[ 35 ] In our experiments, we found that the expression of CCL20 in the lungs was increased significantly in the presence of propionate and butyrate, and the increased expression of CCL20 in the lungs was responsible for the recruitment of Th17 cells. Although several types of cells, including endothelial cells, epithelia cells, macrophages, and tumor cells in lungs may secrete CCL20, [ 36,38,42 ] we found that endothelial cells were the main contributors of CCL20 production. Some other tissues, such as liver and kidney, also expressed CCL20, while the expression did not increase under the same conditions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…[ 35 ] In our experiments, we found that the expression of CCL20 in the lungs was increased significantly in the presence of propionate and butyrate, and the increased expression of CCL20 in the lungs was responsible for the recruitment of Th17 cells. Although several types of cells, including endothelial cells, epithelia cells, macrophages, and tumor cells in lungs may secrete CCL20, [ 36,38,42 ] we found that endothelial cells were the main contributors of CCL20 production. Some other tissues, such as liver and kidney, also expressed CCL20, while the expression did not increase under the same conditions.…”
Section: Discussionmentioning
confidence: 82%
“…The above results indicated that propionate and butyrate treatment promoted the recruitment of Th17 cells and CCL20 expression in the lungs. Previous studies reported that several types of cells in the lungs could secret CCL20, for example, endothelial cells, [ 36,37 ] epithelial cells, [ 38,39 ] macrophages, [ 40 ] and tumor cells. [ 41,42 ] To investigate which type of cell secrets CCL20, the endothelial cell line MS1, epithelial cell line MLE12, macrophage cell line Raw264.7, and B16F10 tumor cells were used.…”
Section: Resultsmentioning
confidence: 99%
“…Next, TargetScan, miRBase and miRTarBase were applied to predict the potential target genes of miR-766-3p ( Figure 4(a) ). We found 28 potential target genes and selected S1PR3, which is associated with the Ras/pERK and PI3K/AKT pathways [ 24 , 25 ] reported in psoriasis and plays role in pro-inflammatory cytokine regulation [ 26 ]. We found that expression of S1PR3 was downregulated in psoriasis tissue (Figures 4(b) and 4(c) ).…”
Section: Resultsmentioning
confidence: 99%
“…According to previous reports, 16,17 human bronchial epithelial cell line (BEAS-2B) was purchased from the Cell Bank of the Chinese Academy of Sciences (Shanghai, China) and cultured in Roswell Park Memorial Institute (RPMI)-1640 medium (Gibco, Rockville, Maryland, USA) supplemented with 10% fetal bovine serum (Sigma-Aldrich, St. Louis, Missouri, USA) at 37 C in a 5% CO 2 incubator (Thermo Fisher Scientific, Waltham, Massachusetts, USA). Cells were treated as shown in Table 1.…”
Section: Cell Culture and Treatmentmentioning
confidence: 98%